2019
DOI: 10.3390/ani9090632
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Mechanistic Insights into the Role of Sweet Potato Vine on Improving Health in Chinese Meishan Gilt Model

Abstract: Simple SummarySweet potato vine as a source of fiber had been used in China for many years. We investigated the effects of fresh sweet potato vine on intestinal and plasma metabolites as well as colon microbial composition in Chinese Meishan gilts. Results suggest that sweet potato vine promoted intestinal muscle development, decreased gut permeability, endotoxin and pro-inflammatory cytokines concentrations, and increased butyrate production as well as beneficial flora, thus improving gut health.AbstractThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The increased gene expressions of TNF-α, IL-6, and IFNγ were noticed in salmonella-challenged pigs [36]. It has been reported that lactic acid bacteria downregulate the gene expression of inflammatory cytokines [37]. In addition, the higher number of eosinophils in pigs fed the Con diet may be responsible for higher gene expression of cytokines.…”
Section: Discussionmentioning
confidence: 91%
“…The increased gene expressions of TNF-α, IL-6, and IFNγ were noticed in salmonella-challenged pigs [36]. It has been reported that lactic acid bacteria downregulate the gene expression of inflammatory cytokines [37]. In addition, the higher number of eosinophils in pigs fed the Con diet may be responsible for higher gene expression of cytokines.…”
Section: Discussionmentioning
confidence: 91%
“…Our findings revealed that Firmicutes and Bacteroidetes are the most abundant phylum in sow’s intestines, accounting for more than 90% of the total sequence, which is consistent with an earlier study ( Kim et al, 2012 ; Poole et al, 2013 ). Firmicutes and Bacteroidetes play a critical role in maintaining the normal physiological function of the intestinal tract and microbial balance, which is of great significance to the growth and health of animals ( Armougom and Raoult, 2008 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…China is the main producer of these two crops with a crop yield of 53 million and 17.73 million tons per year (FAOSTAT, 2020 ), necessarily with large biomass of their byproducts produced, which could be an important feed resource if well used. In practice, dietary inclusion of fresh SPV could promote follicular development of Chinese Meishan gilt and increase beneficial flora abundance (Xu et al, 2019 ; Zhang et al, 2019 ), and supplementing SPV to goats fed grass hay-based diet could improve growth performance and carcass traits, spare conventional concentrate, and improve production benefits (Tadesse et al, 2013 ). Likewise, PS contains about 60% total digestible nutrients and 14% crude protein along with medium fiber level (Sallam et al, 2019 ), and it could be used as a sole diet in goat feeding (Yusiati et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%